2021
DOI: 10.3389/fpsyt.2021.644899
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Exposure, Psychological Distress, Emotion Regulation, and Depression During the COVID-19 Outbreak in Community Samples in China

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) has been a global emergency, affecting millions of individuals both physically and psychologically. The present research investigated the associations between social media exposure and depression during the COVID-19 outbreak by examining the mediating role of psychological distress and the moderating role of emotion regulation among members of the general public in China. Participants (N = 485) completed a set of questionnaires online, including demographic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 76 publications
(120 reference statements)
4
14
1
2
Order By: Relevance
“…Therefore, cognitive reappraisal has a mediating impact on emotion in that it allows individuals to assume a positive rather than a negative perspective toward a certain event, which could help them alter their emotional response and promote their mental health ( McRae, 2016 ). In addition, our results also revealed that none of loneliness, depression or resilience in this study was associated with expressive suppression which was consistent with one recent study ( Tyra et al, 2021 ), but inconsistent with prior studies that expressive suppression was significantly associated with higher loneliness ( Gubler et al, 2020 ) and greater depression ( Zhang et al, 2021 ). One possibility was that there was no insufficient time to develop severe depressive symptoms which made the relationship of expressive suppression with loneliness and depression be difficult to be detected at the assessment.…”
Section: Discussioncontrasting
confidence: 80%
“…Therefore, cognitive reappraisal has a mediating impact on emotion in that it allows individuals to assume a positive rather than a negative perspective toward a certain event, which could help them alter their emotional response and promote their mental health ( McRae, 2016 ). In addition, our results also revealed that none of loneliness, depression or resilience in this study was associated with expressive suppression which was consistent with one recent study ( Tyra et al, 2021 ), but inconsistent with prior studies that expressive suppression was significantly associated with higher loneliness ( Gubler et al, 2020 ) and greater depression ( Zhang et al, 2021 ). One possibility was that there was no insufficient time to develop severe depressive symptoms which made the relationship of expressive suppression with loneliness and depression be difficult to be detected at the assessment.…”
Section: Discussioncontrasting
confidence: 80%
“…Every time a vaccine-related adverse event occurs, it may cause a decline in positive sentiment among Chinese internet users on Weibo, which is highly contagious on social media. Meanwhile, spreading false and appalling information on Weibo, which may bring about feelings of depression and anxiety for certain groups of people [ 58 , 59 ]. Therefore, when a COVID-19 emergency occurred in their particular region, people’s sense of fear and self-protection led to increased positive emotions toward vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to passively following the COVID-19 preventive measures issued by governments and health authorities [e.g., the United States Centers for Disease Control and Prevention (CDC), WHO], one common way to enhance pragmatic and epistemic control is to search for information in an attempt to instantly mitigate the heightened anxiety, threat, and fear elicited by the pandemic. In today's digital era, the sheer volume of information flow can be emotionally taxing for information consumers ( 10 ).…”
Section: Coping With Uncertainty and Anxiety Aroused By The Covid-19 Pandemicmentioning
confidence: 99%